PHYLOGENY ANALYSIS OF BALI ISOLATES OF NEWCASTLE DISEASE VIRUS IN 2013 TO 2014 BASED ON CLEAVAGE SITE OF THE FUSION PROTEIN - Rell, Fedri; Adi, Anak Agung Ayu Mirah; Mahardika, I Gusti Ngurah Kade (Buletin Veteriner Udayana, 2021)
Newcastle disease is a contagious disease caused by the Avian paramyxovirus serotype 1 virus, which infected the poultry. The aims of this study were conducted to phylogenetic analysis  of the fusion  protein  cleavage site of Newcastle disease virus found in a chicken farm in the province of Bali throughout the year 2013 to 2014. There are four isolates from sick chicken’s cases/death suspected of being infected by the Newcastle disease virus. The sequence of the protein fusion was aligned and edited using MEGA5. The amino acid sequence of the F cleavage site of all isolates was 112R-R-Q-K-R-F117 and analysis of phylogeny tree, which justified that all four are virulent of Newcastle disease virus. It is concluded that four Bali isolates in 2013 to 2014 under this study are Newcastle disease virus of genotype VII.